2018
DOI: 10.1007/s00127-018-1638-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety disorders and symptoms in people with hearing impairment: a systematic review

Abstract: Purpose Anxiety disorders are common. Prevalence is likely to be raised in people with hearing impairment, who experience higher rates of associated risk factors. We conducted, to our knowledge, the first systematic review of the prevalence and correlates of anxiety in people with hearing impairment. Methods We searched electronic databases and references of included studies, using predetermined criteria to retrieve original research reporting prevalence of anxiety disorders or symptoms in adult, hearing impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 32 publications
(116 reference statements)
2
37
0
2
Order By: Relevance
“…These findings are in keeping with multiple previous studies, which have found that both hearing and visual impairment are associated with depressive and anxiety symptomatology. 4,13,[25][26][27][28] Our finding that the difference in CIS-R score is greater in younger people might reflect the fact that younger people with sensory impairment are more likely to be different to their peers in this regard, and to miss out on opportunities throughout life. 29 It appears from our results that the association between all types of sensory impairment and common mental illness might be partially accounted for by self-perceived social functioning.…”
Section: Discussionmentioning
confidence: 89%
“…These findings are in keeping with multiple previous studies, which have found that both hearing and visual impairment are associated with depressive and anxiety symptomatology. 4,13,[25][26][27][28] Our finding that the difference in CIS-R score is greater in younger people might reflect the fact that younger people with sensory impairment are more likely to be different to their peers in this regard, and to miss out on opportunities throughout life. 29 It appears from our results that the association between all types of sensory impairment and common mental illness might be partially accounted for by self-perceived social functioning.…”
Section: Discussionmentioning
confidence: 89%
“…Hearing loss in adults has an impact on verbal communication and increases social exclusion and the risk of development of cognitive and functional impairments, particularly among older people (≄65) [15]. Furthermore, adults with hearing loss can experience greater dependence on others, and increased vulnerability to neglect, discrimination or violence [16]. Consequently, age‐related hearing loss is often associated with sadness, feelings of low self‐worth or guilt, a loss of interest in daily activities, and disturbed appetite or sleep, which affect concentration [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although PTSD and hearing loss both contribute significantly to the overall health burden in the military, their co-occurrence has not been widely described in the literature [20]. A VA study by Swan and colleagues was the first to suggest the association, finding that those with a diagnosis of hearing loss were more likely to have a diagnosis of PTSD [21].…”
mentioning
confidence: 99%